Implementasi Supervisi Akademik untuk Meningkatkan Mutu Guru di SMK 1 Babat Supat - Nina Anggraeni; Bukman Lian; Meilia Rosani (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the implementation of academic supervision management functions by the principal to improve teacher quality at SMK Negeri 1 Babat Supat. The research method employed is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results show that the principal systematically implements the planning, execution, and evaluation functions of academic supervision. Planning is conducted through the development of structured supervision programs, execution involves direct observation of the teaching process, and evaluation provides feedback and recommendations for teacher improvement. This supervision implementation positively impacts the enhancement of teachers' pedagogical and professional competencies, ultimately improving the quality of learning. This study recommends further training for principals in the field of academic supervision to support the sustainability of educational quality improvement.